A NEW APPROACH TO VIRTUAL EDUCATION - Vladimir V. Kureychik; Andrey A. Lezhebokov; Sofya V. Pashenko (Открытое образование (Москва))
The article discusses several approaches to training, namely the virtual. Concrete examples of virtual learning systems were described, we disclosed their features, advantages and disadvantages. A new suggested approach integrates the features of existing systems, and opens new horizons and opportunities to obtain certain skills and abilities. Introduction of a new approach to the educational process will improve the quality and effectiveness of learning.